EVALUATION OF IMPLEMENTATION QUALITY ASSURANCE PROGRAM IN ELEMENTARY – JUNIOR HIGH SATAP 2 LINGSAR INTEGRAL BASIC EDUCATION SCHOOL 19 WEST LOMBOK - Untari, Titin -; Karnati, Neti; Suryadi, Suryadi (Journal of Education Research in Administration and Management (JERAM), 2018)
This research aims to know the implementation of quality assurance program in basic education which focused on need analysis, vision, mission and scholl purpose. In order to assure the quality, human resources preparation, program achievement process, quality assurance program achievement, and financial education. This research used evaluation method by using DEM which using descriptive qualitative approach. Data collection prosedure using interview, observation, and documentation. Research informan are headmaster, teachers, staff, student, and scholl committe. Data validity using data source and method triangulation. The result of this research shown that the implementation of quality assurance program for need analysis, vission, mission, and scholl purpose very good. Human resource have been good. Quality assurance achievement very good. Financial which related with program reports and controlling very good. So, me can conclude that the implementation of quality assurance classified into good category.   Keywords : program evaluation, quality assurance